UNIVERSITY RANKING IMPROVING TOOLS IN MODERN INFORMATION EDUCATIONAL ENVIRONMENT - M. Bilous (Ìнформаційні технології в освіті, 2015)
Ranking criteria of national and international levels are the instruments of university ranking increasing. Ratings provide a balanced measure of quality in higher educational institutions. Determining the level of university research influences the position of the university in various rankings. We can separate the main aggregates that are considered when ranking international higher education institutions. The results of university ranking allows the identification of its strengths and weaknesses in order to develop strategies for success and excellence based on the achievements of other universities at the regional, national and international levels. In article, we can see strengths, weaknesses, opportunities, and threats of Kherson State University (SWOT-analysis). The main goals of Kherson State University are self-promotion in the media space, raising the prestige of KSU and integration with the world science community, development of an effective technological corridor: «School - University – Labor» market, increasing the number of students, improving the ranking of academic staff in scientometric databases, and gaining international recognition.